1998
DOI: 10.1080/096392898331225
|View full text |Cite
|
Sign up to set email alerts
|

TEACHING RESOURCE Using MONOPOLY TM and Teams-GamesTournaments in accounting education: a cooperative learning teaching resource

Abstract: A three-week financial accounting simulation was conducted using university accounting majors (n=36) in one section of a junior-level financial reporting issues course. The curriculum involved using the board game Monopoly as a teaching resource in cooperative learning teams. Findings indicate students' attitudes toward financial accounting and learning, mutual concern for fellow students and perceived achievement were very positive upon completion of this cooperative learning exercise. Additionally, gender an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 18 publications
2
23
0
1
Order By: Relevance
“…Consistent with the investigation by Tanner and Lindquist (1998), this study indicates that computer-based gaming within Teams-Games-Tournament cooperative goal structure facilitated students' attitudes toward learning. This finding confirms Johnson and Johnson's (1996) and Slavin's (1995) claim that cooperative experiences promoted higher self-esteem than competitive or individualistic experiences did.…”
Section: The Effect Of Alternative Game-based Learning Situations On supporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with the investigation by Tanner and Lindquist (1998), this study indicates that computer-based gaming within Teams-Games-Tournament cooperative goal structure facilitated students' attitudes toward learning. This finding confirms Johnson and Johnson's (1996) and Slavin's (1995) claim that cooperative experiences promoted higher self-esteem than competitive or individualistic experiences did.…”
Section: The Effect Of Alternative Game-based Learning Situations On supporting
confidence: 88%
“…Despite the large number of studies about the use of classroom goal structure alone and computer games alone, few empirical studies examine the interaction between the two variables (Cavalier and Klein 1998;Tanner and Lindquist 1998). Closely related to the current study is Bahr and Rieth's (1989) investigation of a computer-based arithmetic drilland-practice game designed to increase single-digit computation fluency.…”
Section: Individual Differences In Game-based Learningmentioning
confidence: 88%
“…Classroom goal structures for computer games Consistent with the investigation by Tanner and Lindquist (1998), this study indicates that Teams-Games-Tournament cooperative goal structure is most helpful in sustaining the motivational effects of computer games. This finding also supports the speculation based on cognitive evaluation theory (Deci et al 1999) that the intrinsic motivation appeal of computer-based games is mediated by the external reward structures (in this case, classroom goal structures).…”
Section: Computer Games Application 553supporting
confidence: 84%
“…A recent review revealed only a few comparative studies conducted years ago (e.g., Bahr and Rieth 1989;Strommen 1993;Tanner and Lindquist 1998).…”
Section: Empirical Research On Classroom Goal Structures For Gamingmentioning
confidence: 99%
See 1 more Smart Citation